Роль та значення принципів права в системі права - Шаганенко, В.П. (Альманах права, 2012)
В статті запропоновано систему принципів, які визначають формування системи права та її структуру, зокрема, такі принципи: єдності класифікаційних критеріїв системи права; взаємовиключення елементів системи права; виділення базису системи права; виділення підсистем приватного й публічного права; виділення підсистем регулятивних і охоронних галузей права. В статье предложено систему принципов, которые определяют формирование системы права и ее структуру, в частности, следующие принципы: единства классификационных критериев системы права; взаимоисключения элементов системы права; выделение базиса системы права; выделение частного и публичного права; выделение подсистем регулятивных и охранительных отраслей права. The paper proposed a system of principles that determine the formation of the legal system and its structure, in particular, the principles are: unity of the classification criteria of law, mutual exclusion elements of the law, the selection of the basis of law, separation of private and public law, the selection of subsystems and regulatory enforcement branches of law. The necessity of forming a system of law with regard to the unity of the classification criteria of rights is indisputable: a vast array of legal norms that form a system of law requires some adjustment and organization. It is noted that the objective prerequisites for building a legal system is the existing social relations within the regulation. One element of the law claimed to be the foundation, the basis of the system, of course, must cover virtually all or a significant majority of public relations. It is this feature has constitutional law, regulations and legal provisions which are the basis and find their development in other areas of domestic law. It is ascertained that in legal science research trend right direction depending on the functional regulation of social relations and selection on this basis, areas of law with regulatory and protective functions. This new direction for legal science requests deep understanding of the classification and determine the place and role of each subsystem of law. Noted that one can not simply transfer the law, to mark their place in the subsystem and system of law in general, to identify them, mutual and mutual influence, and give each area of law characteristics that will help not only to build a modern system of law, but also to predict the emergence of possible legal sectors and institutions in the future.